2021
DOI: 10.4274/jcrpe.galenos.2020.2020.0125
|View full text |Cite
|
Sign up to set email alerts
|

The IGSF1 Deficiency Syndrome May Present with Normal Free T4 Levels, Severe Obesity, or Premature Testicular Growth

Abstract: Our objective was to further expand the spectrum of clinical characteristics of the IGSF1 deficiency syndrome in affected males. These characteristic include almost universal congenital central hypothyroidism (CeH) with disharmonious pubertal development (normally timed testicular growth, but delayed rise of serum testosterone), macroorchidism, increased body mass index (BMI), and decreased attentional control. In addition, a subset of patients show prolactin deficiency, transient partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 43 C-C motif chemokine ligand 2 (CCL2) was observed to be associated with the risk of myocardial infarction. 44 Genes include secreted phosphoprotein 1 (SPP1), 45 and immunoglobulin superfamily member 1 (IGSF1) 46 plays an important role in obesity. Kiczak et al 47 found that TIMP (Tissue inhibitor of metalloproteases) metallopeptidase inhibitor 1 (TIMP1) might affect the prognosis of patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“… 43 C-C motif chemokine ligand 2 (CCL2) was observed to be associated with the risk of myocardial infarction. 44 Genes include secreted phosphoprotein 1 (SPP1), 45 and immunoglobulin superfamily member 1 (IGSF1) 46 plays an important role in obesity. Kiczak et al 47 found that TIMP (Tissue inhibitor of metalloproteases) metallopeptidase inhibitor 1 (TIMP1) might affect the prognosis of patients with HF.…”
Section: Discussionmentioning
confidence: 99%